Penerapan Undang-Undang Kepailitan dalam Menciptakan Iklim Berusaha Yang Sehat Bagi Seluruh Pelaku Usaha - Syafrudin Makmur (Universitas Serang Raya, 2018)
Law Number 37 Year 2004 concerning Bankruptcy and Postponement of Debt Payment Obligation (PKPU) is enacted in good faith to protect the rights of creditors who have receivables on the insolvent party, since in general the assets left by the insolvent party is less than the amount of the debt . So that the condition is very potential to cause chaos if the number of creditors more than one, because they each will fight each other to control the assets left behind as compensation for the settlement of receivables, and eventually among the creditors will apply: